Emotion regulation, resilience, and mental health: A mediation study with university students in the pandemic context - Brites, Rute Sofia Ribeiro (2023)
The COVID‐19 pandemic had a huge impact on people'slives due to the fear of getting infected and having thedisease, as well as the necessary prevention and contain-ment measures. University students were one of the mostaffected groups, as they were forced to cope withsignificant life changes. However, not all displayedsymptoms of psychological distress, which means thatinternal resources such as emotional regulation andresilience may have acted as protective variables. Thiscross‐sectional study aimed to examine the extent towhich the relationship between emotion regulation andstress, anxiety, depression, and posttraumatic stressdisorder (PTSD) symptoms was mediated by resilience ina sample of university students. Results showed thatemotion regulation strategies were positively associatedwith lower mental health. Some resilience dimensionsmediated these relationships, with perception‐of‐selfmediating all associations. Planned future mediated theassociation between emotion regulation and depression,family cohesion mediated the relation between emotionregulation and stress, and social resources mediated theassociation of cognitive reappraisal with anxiety and PTSDby suppressing the direct positive relationship. ThesePsychol Schs. 2024;61:304–328.wileyonlinelibrary.com/journal/pits304 | © 2023 Wiley Periodicals LLC.This manuscript comprises original, unpublished material and is not under consideration for publication elsewhere. The primary data have not beenpublished previously nor accepted for publication. results highlight the relevance of resilience as a keyresource in coping effectively with the uncertainties, andchanges that arise during stressful periods such as apandemic.